Proposed OFDM Modulation for Future Generations of GNSS Signal System. (8th March 2016) - He, Ting; Ma, Zherui
Abstract : Modulation design has a significant effect on the accuracy of a navigation system. Two problems exist in current modulations for Global Navigation Satellite Systems (GNSS). One is the extremely low transmission rate of navigation messages. The other is the pseudorange error caused by multipath. To solve the restrictions, a novel GNSS signal system is proposed in this paper. In the new signal system, navigation messages are modulated by Orthogonal Frequency Division Multiplexing (OFDM) modulation for high transmission rate as well as excellent anti-multipath performance and conventional ranging code is still transmitted by Phase Shift Keying-Rectangular (PSK-R) or Binary Offset Carrier (BOC) modulation for precise ranging. Both the signal components supplement each other. Simulation results show that using the proposed GNSS signal system, stable and high transmission quality along with high transmission efficiency for navigation data are achieved. Also, the anti-multipath performance is significantly improved with less computational complexity.